'Without an Aadhaar card nothing could be done': a mixed methods study of biometric identification and birth registration for children in Varanasi, India. Issue 1 (2nd January 2021) - Bhatia, Amiya; Donger, Elizabeth; Bhabha, Jacqueline
ABSTRACT: Research on the global growth of digital identification programs has been largely silent on the implications for children and on birth registration. We conducted a mixed methods study with children, caregivers, and service providers in the Indian city of Varanasi to examine access to, and perceptions of, birth registration and Aadhaar. Findings show enrollment in Aadhaar far exceeds birth registration for both children and their caregivers, and that many respondents believe that Aadhaar enrollment is mandatory, and equates to securing proof of citizenship. Respondents described similar challenges with birth registration and Aadhaar, including that both can be falsified to support child labor and child trafficking. We suggest that promoting Aadhaar enrollment over birth registration undermines the critical role of birth registration in providing the state with comprehensive and actionable public health data. Links between birth registration and Aadhaar should be strengthened and their role in advancing child protection more closely examined.